Regionally acquired intestinal failure data suggest an underestimate in national service requirements. Issue 12 (17th August 2009) - Barclay, A R; Paxton, C E; Gillett, P; Hoole, D; Livingstone, J; Young, D; Menon, G; Munro, F; Wilson, D C
Abstract : Objectives, setting and patients: With complete case referral for prolonged parenteral nutrition (PN) beyond term equivalent, serving a stable population of 1.25 million people, we describe the long-term outcome and survival of patients referred to an intestinal failure (IF) nutrition support team over the first 8 years of existence at a regional paediatric centre, and extrapolate to potential numbers of national home parenteral nutrition (HPN) cases and intestinal transplantation data. Design and outcome measures: Retrospective analysis detailing patient demographics, interventions, use of HPN, occurrence of intestinal failure-associated liver disease (IFALD), and outcomes of enteral adaptation, survival, and referral for and receipt of organ transplantation. Results: 23 patients were referred over 8 years, 20 being PN dependent within the neonatal period. Diagnoses included short bowel syndrome (SBS) (18), neuromuscular abnormalities (4) and congenital enterocyte disorder (1). 12 696 days of PN were delivered with 314 confirmed episodes of sepsis at a median of 12 episodes per patient. 144 central venous catheters (CVCs) were required at a median of four per patient. IFALD occurred in 17 (73%) patients, with 10 (44%) referred for transplant assessment. Thirteen (56%) children received HPN. Overall mortality was 44%. A significant predictor for survival in the SBS group was residual bowel >40 cm (82% vs 28%, p = 0.049). Conclusions: Survival for IF at 56% was lower than reported from non-UK supra-regional centres, and nationally collected data, possibly reflecting pre-selected referral populations. Data from regional centres with complete ascertainment may be important both when counselling parents and when planning regional and national HPN and IF specialist services.